Analysis of Drought Index in Sub-Urban Area Using Standard Precipitation Evapotranspiration Index (SPEI) - R. Azman, R. M. N.; M. Noor, N. A.; Abdullah, S.; Ideris, M. M. (International Journal of Integrated Engineering, 2022)
The climate change interference and increase of surface temperature have contributed to the changes at the atmosphere that give a significant effect to the availability of water. Malaysia is one of the countries which effected with this event and had been suffered series of drought events in 1997, 1998, and 2014. These problems contribute to the disruption of country’s economic development and quality of life. The using of drought indices for analytical is important and it can estimate the drought affect hat are being experienced accurately. The Standard Precipitation Evapotranspiration Index (SPEI) is one of the methods in determination of drought indices. Thus, the objective of this paper is to determine the drought index using the Standard Precipitation Evapotranspiration Index (SPEI) for sub-urban river basin which is Pahang River basin. The rainfall and potential evapotranspiration (PET) data were obtained from Malaysian Meteorological Department (Met Malaysia) starting from 1988 until 2018 in determining the SPEI value for sub-urban river basin. RStudio software are being used to determine the value of SPEI for different timescale, which is 3, and 12-month. The significant value of SPEI for the river basin are influence by the population, topography, rainfall, and land use. Findings from this study are believed to the mitigation can be proposed to the related organization to take an action in designing, planning, and managing the water supply and to prevent the serious impact on the agricultural and country economic development as well.